2014
DOI: 10.1021/ie500442r
|View full text |Cite
|
Sign up to set email alerts
|

Study of AgLiLSX for Single-Stage High-Purity Oxygen Production

Abstract: Commercial adsorbents do not exhibit argon/oxygen equilibrium selectivity above 1. However, in the past decade, Air Products and Chemicals developed an argon/oxygen selective silver-based zeolite, AgLiLSX. In this contribution, the authors studied and characterized the AgLiLSX adsorbent to provide fundamental data to evaluate its potential for high-purity oxygen production in a single-stage PSA unit. Oxygen, nitrogen, and argon adsorption isotherms and breakthroughs curves were obtained, and moderate equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Ag-mordenite has been reported as having values of 17% and 0.062 cm 3 g À1 , 28 AgLiLSX has 27% and 0.118 cm 3 g À1 (ref. 61) and Ag-ETS-10 has 38% 31,62 and 0.13 cm 3 g À1 . 63,64 The low porosity of the dipeptides is a contingent property, which does not need to exist in other materials with unidimensional pores, even for such small pores; it stems mostly from the low pore concentration existent in the dipeptides, 0.45 pores nm À2 to 0.48 pores nm À2 .…”
Section: Significance Of Psa Separation In Airmentioning
confidence: 99%
“…Ag-mordenite has been reported as having values of 17% and 0.062 cm 3 g À1 , 28 AgLiLSX has 27% and 0.118 cm 3 g À1 (ref. 61) and Ag-ETS-10 has 38% 31,62 and 0.13 cm 3 g À1 . 63,64 The low porosity of the dipeptides is a contingent property, which does not need to exist in other materials with unidimensional pores, even for such small pores; it stems mostly from the low pore concentration existent in the dipeptides, 0.45 pores nm À2 to 0.48 pores nm À2 .…”
Section: Significance Of Psa Separation In Airmentioning
confidence: 99%
“…The rise in the number of patents and articles on portable medical oxygen concentrators, specifically by Sircar et al, in the recent years reflects the interest in developing new materials as well as adsorption processes to purify oxygen from air [3][4][5][6][7]. In addition to this, industries such as aerospace, semiconductors, military, and medical require the production of on-site oxygen with ultra-high purity (> 99.5%) [8]. It has been demonstrated that adsorption processes offer more favorable process economics as well as meeting the purity and throughput requirements for small-scale O 2 purification [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many niche applications in medical, semiconductor, military, and aerospace industries require O 2 purities in excess of 95%. ,− For such applications, special sorbents that show oxygen/argon selectivity are required. Very few adsorbents such as carbon molecular sieves, , Ag-mordenite, , Ag-ZSM, and AgLiLSX have been reported to possess this selectivity. Because the properties of O 2 and Ar are very similar, the reported O 2 /Ar selectivities are typically less than 1.29.…”
Section: Introductionmentioning
confidence: 99%